ANALISIS EFEKTIVITAS DAN EFISIENSI PENERIMAAN RETRIBUSI TERMINAL SERTA PROSPEKNYA DI KOTA DENPASAR - Ni Made Yusmini; Kadek Dwi Indriani Utami (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
Denpasar City as the Capital of the Province of Bali is a center of social, economic activity and tourism destinations. Terminal levies as a source of regional revenue need to be developed and assessed for effectiveness, efficiency and prospects as a basis for making optimal terminal service management policies. The purpose of this study was to determine the level of effectiveness of terminal retribution receipts in Denpasar City, to determine the level of efficiency of terminal retribution receipts in Denpasar City and to determine the prospects of terminal retribution receipts in Denpasar in 2009-2014. The data used in this study are secondary data collected from related agencies within 5 (five) years from 2004-2008. The analysis used in this study is the analysis of effectiveness, efficiency, and prospects. The analysis shows that the level of effectiveness of terminal retribution receipts based on targets set from 2004-2008 averaged 101.04 percent which is in the very effective category, The average level of efficiency in managing terminal fees in Denpasar from 2004-2008 is classified as inefficient, because it is above 100 percent, even reaching an average of 110.48 percent, and prospects / estimates of terminal retribution receipts in Denpasar City in 2009-2014 amounting to Rp 1,376,903,828, Rp 1,632,462,579, Rp1,888,021,330, Rp 2,143,580,081, Rp 2,399,138,832, Rp 2,654,697,583.